The crystallization process in the nano-iron particles model - Nguyen , Trong Dung; Nguyen , Chinh Cuong (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This paperstudiesthe microstructure and the crystallization processin the nano-iron particles modelwith 10,000particlesat temperatures 300K, 500K, 700K, 900K, 1000K and 1,100K.The modelwas studied by Molecular Dynamics method (MD) with the Pak-Doyama pair-interaction potential andaperiodicboundary conditions. The microstructure characteristics was analyzed by the radial distribution function (RDF), the size, the energy and the coordination number. The crystallization process was studied through the relationships between the energy and the number of thermal annealing steps, between the number of crystal nucleation and the coordination number, between the number of crystal nucleation with the radius and showed that temperature of crystallization process from 907K to 998K.